Teachers’ Practices in Fostering Children’s Critical Thinking at Pre-Primary Level in Kongwa District - Kwambaza, Clement Peter (Central European Journal of Educational Research, 2024)
Critical thinking skills is one of the most important 21st century skills and one of the most vital indicators of the quality of education children are receiving. In enhancing these important skills, it is very important to unfold teachers’ practices in fostering children’s critical thinking skills. Therefore, this study investigated teachers’ practices in fostering children’s critical thinking skills in pre-primary level in the Kongwa District of the Dodoma Region, Tanzania. The study employed a qualitative research approach with a phenomenography research design. The total sample of the study was 35 respondents, selected through the criterion purposive sampling technique. Data were collected through in-depth interviews and classroom observation. Data analyses were done through the thematic analysis framework of Braun and Clarke (2021). The findings revealed that teachers’ practices which include teachers’ preparations, the use of instructional strategies, social activities, teaching and learning materials, and creating classroom learning environment helps children to think critically. The study recommends the quality assurers should maintain monitoring and supervision of teachers’ classroom practices in promoting the critical thinking skills of children.